2017
DOI: 10.3906/biy-1704-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of phenolics in natural and micropropagated plantlets of Thymus pseudopulegioides Klokov & Des.-Shost. with their antioxidant potentials

Abstract: The in vitro production of rosmarinic acid (RA), an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid, has particular importance as it has always been included in important phenolics lists owing to its antioxidant, antiinflammatory, anticancer, and antidiabetic properties, make it attractive in the food industry as well as complementary medicine (Petersen and Simmons, 2003).The organic synthesis of RA is tedious, time-consuming, and costly (Chapado et al., 2010;Brahmachari, 2013). Therefore, producers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The antioxidant activity of phenolics is mainly originates from their redox properties, which allow them to act as reducing agents, hydrogen donators, and singlet oxygen quenchers (Ozen, Demirtas, & Aksit, 2011). DPPH radical scavenging activity of T. pseudopulegioides leaf was found to be in consistent with a previous study reported by Günaydin et al (2017), who reported that IC50 values of natural (wild) T. pseudopulegioides collected from Anzer Mountain is 4.89 µg/mL. In another study, higher free radical scavenging activity (IC50 value 36.77 µg/mL) of the ethanolic extracts from Thymus vulgaris was reported (Gedikoglu et al, 2019).…”
Section: Antioxidant Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…The antioxidant activity of phenolics is mainly originates from their redox properties, which allow them to act as reducing agents, hydrogen donators, and singlet oxygen quenchers (Ozen, Demirtas, & Aksit, 2011). DPPH radical scavenging activity of T. pseudopulegioides leaf was found to be in consistent with a previous study reported by Günaydin et al (2017), who reported that IC50 values of natural (wild) T. pseudopulegioides collected from Anzer Mountain is 4.89 µg/mL. In another study, higher free radical scavenging activity (IC50 value 36.77 µg/mL) of the ethanolic extracts from Thymus vulgaris was reported (Gedikoglu et al, 2019).…”
Section: Antioxidant Activitysupporting
confidence: 90%
“…Shost" is one of the important aromatic species of Thymus genus that is an endemic species and has been growing widely in Turkey, especially on the Eastern Black Sea Region. It is known as Anzer tea (Rize) and Anuk (Trabzon) by local people (Günaydin, Laghari, Bektaş, Sökmen, & Sökmen, 2017). The people living in the Eastern Black Sea Region consume this plant as tea.…”
Section: Introductionmentioning
confidence: 99%